Surface-electrode ion traps for scalable quantum computing - Allcock, D (2011)
The major challenges in trapped-ion quantum computation are to scale up few-ion experiments to many qubits and to improve control techniques so that quantum logic gates can be carried out with higher fidelities. This thesis reports experimental progress in both of these areas. In the early part of the thesis we describe the fabrication of a surface-electrode ion trap, the development of the apparatus and techniques required to operate it and the successful trapping of 40Ca+ ions. Notably we developed methods to control the orientation of the principal axes and to minimise ion micromotion. We propose a repumping scheme that simplifies heating rate measurements for ions with low-lying D levels, and use it to characterise the electric field noise in the trap. Surface-electrode traps are important because they offer a route to dense integration of electronic and optical control elements using existing microfabrication technology. We explore this scaling route by testing a series of three traps that were microfabricated at Sandia National Laboratories. Investigations of micromotion and charging of the surface by laser beams were carried out and improvements to future traps are suggested. Using one of these traps we also investigated anomalous electrical noise from the electrode surfaces and discovered that it can be reduced by cleaning with a pulsed laser. A factor of two decrease was observed; this represents the first in situ removal of this noise source, an important step towards higher gate fidelities. In the second half of the thesis we describe the design and construction of an experiment for the purpose of replacing laser-driven multi-qubit quantum logic gates with microwave-driven ones. We investigate magnetic-field-independent hyperfine qubits in 40Ca+ as suitable qubits for this scheme. We make a design study of how best to integrate an ion trap with the microwave conductors required to implement the gate and propose a novel integrated resonant structure. The trap was fabricated and ions were successfully loaded. Single-qubit experiments show that the microwave fields above the trap are in excellent agreement with software simulations. There are good prospects for demonstrating a multi-qubit gate in the near future. We conclude by discussing the possibilities for larger-scale quantum computation by combining microfabricated traps and microwave control.